Does foreign direct investment cause economic growth? Panel data evidence from transition economies - (:unkn) unknown (ASERS Publishing House, 2015)
The paper examines the causal relationship between foreign capital investments and economic growth for 27 countries known as the transition economies. In this study, these countries were categorized in two subgroups as Central West Asia (8 countries) and Central Eastern Europe (19 countries) as well as all of 27 countries as the causality was analyzed. The causality between foreign direct investment and growth was investigated by the Panel Granger Causality Analysis and Hurlin-Venet (2001) Panel Causality Analysis in categorized countries. The findings show that there is a causal relationship in the transition economies involved in Central Eastern European Classification from foreign capital investment to economic growth. © 2015, ASERS Publishing House. All rights reserved.
Keywords: Economic growth; Foreign direct investment; Panel causality; Transition economies